Factors influencing catch and support for the implementation of the closed fishing season in Davao Gulf, Philippines. (August 2021) - Macusi, Edison D.; Liguez, Arianne Kay O.; Macusi, Erna S.; Digal, Larry N.
Abstract: The closed fishing season policy is annually imposed in Davao Gulf to allow the fish stocks to recover and address the declining fish catch. Up to now, there were no assessments conducted to determine multiple factors that could have been contributing to its proper implementation in the Davao Gulf. A mixed-methods approach was used through interviews of fishers (N = 229) and supplemented by nine focus groups in Governor Generoso, Lupon, Davao City, Sta. Maria, Don Marcelino and Malita. Results of the regression analysis showed that the catch per unit effort (CPUE) was highly influenced by revenue and number of years of fishing experience (df = 3, MS = 7.38, F  = 47.90, p  < .001). In addition, the main predictors for the support of the imposition of closed fishing season were the number of fishing hours, fish price, membership to community organizations, and awareness of policy among fishers. Economic motivation seems to predominate among fishers as both factors: revenue and fish price, are related and increase due to the imposition of the closed fishing season. The fishing experience and the number of hours of fishing can both determine the catch success of fishers in their fishing grounds. In addition, the flow of information between fishers is usually done through membership with community organizations due to the familiarity of members with one another. Moreover, fisher to fisher interactions also help transmit information in the fishing grounds. Ultimately, the fisher's willingness to cooperate and support the closed fishing season policy will help determine the fish stocks recovery. Highlights: Closed fishing season is essential to help fish stocks recover in Davao Gulf Catch per unit effort (CPUE) was highly influenced by revenue and fishing experience Awareness, membership to organizations, fishing hours and fish price influenced the implementation of the closed fishing season. Economic motivation was also a major reason for the support of the closed fishing season.